Dietary inflammatory index in relation to salivary cytokine concentrations and periodontitis: A cross-sectional analysis - Syrjäläinen Sanna; Männistö Satu; Könönen Eija; Pussinen Pirkko; Gürsoy Mervi; Suominen Anna Liisa; Jousilahti Pekka; Gürsoy Ulvi K. (United States, 2025)
Aim: To examine the associations of dietary inflammatory index (DII) with salivary cytokine concentrations and periodontitis after controlling for body mass index (BMI), socio-demographic factors and lifestyle.
Materials and methods: Subgroups from two Finnish surveys, DILGOM 2007 and Health 2000, were included (total n = 727). The DII scores were calculated based on a food frequency questionnaire. Periodontal status was assessed with a cumulative risk score in DILGOM 2007 and by pocket depth measurement in Health 2000. From saliva, interleukin (IL)-1β, IL-1 receptor antagonist, IL-6, IL-8, IL-10 and tumour necrosis factor (TNF)-α concentrations were measured.
Results: The DII scores did not differ between non-periodontitis and periodontitis participants in pairwise comparison. After adjusting for energy intake, periodontal status, BMI, age, education level, smoking habit and physical activity, DII was not associated with salivary cytokine concentrations. After adjusting for salivary cytokine levels and other confounding factors, DII was associated with periodontitis in the Health 2000 subgroup but not in the DILGOM 2007 subgroup.
Conclusions: The current data support the evidence that diet is not associated with salivary cytokine levels but may be associated with periodontitis. The association observed between diet and periodontitis is related to factors other than diet-dependent inflammatory tendency in the oral cavity.